Meanings of a 'good death' for people with cancer assisted by home care services - Polino Gomes, Marcela (2025)
Introduction: A "good death" is an individual and variable concept that encompasses practices to promote dying and death in a comfortable, dignified manner with the least possible suffering.  Objective: To understand the meanings and describe the aspects involved in a 'good death' for people with cancer assisted by home care services. Method: Qualitative research conducted between December 2022 and January 2023 through semi-structured interviews with seven cancer patients affiliated to a home care and palliative care unit of a hospital in southern Brazil. The data were analyzed according to Creswell's theoretical proposal. Results: Three subcategories were developed: "Dialogues and silences about end of life and death," "Meanings of a good death," and "Care for a good death." In these, it was identified what the interviewees think about their own death, what a good death means to them, and what care is involved in fostering it. Conclusion: The meanings of a good death are attributed to dying at home peacefully, asleep, without pain, and with the presence of family, while care for a good death is mainly linked to receiving love and attention at the end of life.